What educator capabilities are necessary for reflective learning in accounting students? - Ramsarghey, K. (South African Journal of Higher Education, 2020)
One of the main roles of universities is to facilitate quality teaching and learning in accordance with applicable professional and academic standards. Academic departments are required to ensure that qualifying teaching staff possess the necessary experience to offer these qualifications. Accounting lecturers in South African universities are employed based mainly on their Accounting qualifications. However, in order to secure tenure in Accounting academia, the prospective lecturer has to satisfy employment criteria for teaching and learning, research and community engagement. An educator’s approach to teaching determines whether he/she is teacher-centred or student-centred. This article seeks to determine the relationship between educator capabilities and student performance. In discussing this relationship, it is clear that work/industry experience, teaching qualification and teaching experience are intended to satisfy the aspect of teaching and learning which, in turn, is expected to improve student performance. System Dynamics is used as an analytical model to determine the relationship between lecturer capabilities and student performance. The model is used on the three areas of educator capabilities, namely, work experience, teaching qualification and teaching experience as criteria for improving student performance in Accounting education. In the final analysis, this article argues that lecturers who possess these critical qualities tend to be student-centred, which is necessary for reflective learning in students.